Gene structure and expression - Hawkins, John D. (Cambridge University Press, 1996)
This new edition of a highly successful undergraduate text is a concise yet fully informative guide to the structure and function of genes. It describes DNA and how it replicates, how DNA is transcribed and translated into proteins, the organization of genes in prokaryotes and eukaryotes, the control of gene expression, and the role of retroviruses and oncogenes in cancer. There are additional discussions of gene families, genes and the immune systems, and mitochondrial and chloroplast genomes. The new edition has been extensively updated, particularly in regard to recent advances in our understanding of replication and transcription. Undergraduates studying genetics will benefit from this established text.